StOPping Hypertension and imprOving Children’s Lives after KidnEy TranSplantation (SOPHOCLES): study protocol for a randomized controlled multicenter trial - Grabitz, Carl Robert; Memaran, Nima; Sugianto, Rizky; von der Born, Jeanine; Bukova, Mila; Lehmann, Elena; Konuhov, Ann-Kathrin; Holzwart, Dennis; Großhennig, Anika; Wühl, Elke; Schmidt, Bernhard; Melk, Anette (Trials, 2025)
Background - Cardiovascular disease is a major morbidity in children after kidney transplantation, limiting life expectancy and impairing graft function. Arterial hypertension is the dominant cardiovascular risk factor and highly abundant in this patient group. Arterial hypertension can cause left ventricular hypertrophy, which is predictive of cardiovascular death. Left ventricular hypertrophy can be non-invasively assessed by measuring left ventricular mass. Observational data indicated that intensified blood pressure control was associated with a significant reduction of left ventricular mass. Based on evidence from the randomized controlled ESCAPE trial, intensified blood pressure control is recommended in children with chronic kidney disease prior to kidney replacement therapy. However, current treatment recommendations for pediatric kidney transplant patients follow the recommendations for otherwise healthy children and adolescents with arterial hypertension, i.e., suggesting a blood pressure target < 90th percentile. - Methods - In the proposed multicenter, randomized, parallel group trial with blinded endpoint evaluation, we aim to include 170 pediatric patients who underwent a kidney transplantation more than 12 months ago. Patients will be randomly assigned 1:1 to an intensified blood pressure management group (blood pressure target ≤ 60th percentile) and a standard blood pressure management group (blood pressure target < 90th percentile). The primary endpoint is left ventricular mass after 24 months. Secondary endpoints are pulse wave velocity, intima media thickness, estimated glomerular filtration rate, and albuminuria. Achievement of blood pressure targets will be facilitated through blood pressure telemonitoring. Blood pressure values will be transmitted in real time to the treating physician and the trial’s centralized study office allowing timely responses in case blood pressure values lie outside target range. - Discussion - The proposed study will result in an evidence-based definition of blood pressure targets and will therefore have direct implications for the care of children after kidney transplantation. In case intensified blood pressure targets are effective, this should eventually lead to lower cardiovascular morbidity and subsequently lower cardiovascular mortality of pediatric kidney transplant recipients. - Trial registration - ClinicalTrials.gov NCT06589947. Registered on September 6, 2024.
Gesehen am 19.02.2026